Beyond the score: a sequential study on the predictors of student resilience in mathematics problem-solving - Roar A. Callaman; Amelia M. Bonotan (Institute of Advanced Engineering and Science, 2026)
This sequential explanatory study aims to probe on the influences of cognitive, psychological, and social factors on mathematics resilience in problem solving. Anchored on three-dimensional resilience theory in problem solving, stratified sampling and purposive sampling were used to determine the respondents of the study coming from the six large-categorized senior high schools in Davao City (Philippines), school year 2023-2024. Data gathering was administered using the researcher-made questionnaire and interview guide, and content validated by experts. The quantitative findings, through the multiple regression test, revealed that problem-solving skills (PSS), growth mindset (GM), and teacher scaffoldings (TS) significantly predict students’ resiliency in mathematics. For the qualitative data, following Colaizzi’s data analysis, the following themes surfaced: i) GM and positive learning attitudes; ii) active problem-solving strategies; and iii) supportive learning environment (SLE) and TS. The results confirmed that cognitive, psychological, and social factors are significantly related to students’ resiliency in solving mathematics problems and that developing a growth attitude, fostering a SLE, and providing appropriate TS, can help build students’ mathematical resilience and PSS.